Career goals and internship quality among VET students - Gamboa, Vitor (2021)
Given the increased self-directedness of todays' career environment, career goals represent to some extent the exercise of individual agency, particularly during ecological transitions (e.g., school to work). The main purpose of this study was to analyze the relationship between internship quality and career exploration behavior, considering students' career goals content (labor market vs. higher education). Using a longitudinal design (pre- and post-internship), we conducted a study (12th grade; N = 191) that explores the relationship between perceived qualities of the internship and the different dimensions of career exploration. Analysis of variance and analysis of covariance, with repeated measures, were used to analyze the data. The results reinforce the importance of career goals, since they seem to have a differentiating effect on how the quality of the internship interacts with students' career exploration behavior. Finally, the implications of these findings for career interventions and for future research in this area are discussed.